A cellulose dissolution and encapsulation strategy to prepare carbon nanospheres with ultra-small size and high nitrogen content for the oxygen reduction reaction. (12th June 2020) - Zhang, Fuping; Liu, Liu; Chen, Long; Shi, Yulin
Abstract : Space-confined pyrolysis of microcrystalline cellulose (MCC) to prepare ultra-small N-doped carbon nanospheres (NCNs) with high nitrogen content and superior ORR performance. Abstract : We have devised a feasible approach to prepare nitrogen-doped carbon nanospheres (NCNs) with ultrasmall size and high N-doping amount via the dissolution and space-confined pyrolysis of cellulose using ZnCl2 . The results indicated that pyrolysis, gasification, and nitrogen doping of the cellulose occurred in a fully-sealed nanoreactor (inner diameter ≈ 11 nm). The formation of an autogenic pressure inside the nanoreactor played an important role in improving the heteroatomic equilibrium conditions, thereby increasing the nitrogen content (increased to ca. 2 times) and biochar yield (increased by ca. 56.6%). The nitrogen content, nitrogen type and equivalence ratio, as well as the specific surface area, were easily regulated by varying the amount of ZnCl2 . The resulting NCN-7 exhibited a high oxygen reduction reaction (ORR) activity with a half-wave potential ( E 1/2 ) of 0.87 V ( versus the reversible hydrogen electrode, RHE) that surpassed those of most reported biomass-derived catalysts, even those of the commercial Pt-based catalysts (0.86 V). This remarkably improved catalytic activity was attributed to the high total nitrogen content (8.56 at%), pyridinic N concentration (3.06 at%), and large specific surface area (1655.0 m 2 g −1 ) of the catalyst. This work proposes a universal method for the conversion of abundant renewable biomass (including cellulose, chitosan and cotton-stalks) into advanced nanoelectrocatalysts by the dissolution and space-confined pyrolysis strategy.